Comparative genome analysis of Campylobacter fetus subspecies revealed horizontally acquired genetic elements important for virulence and niche specificity. - Sabine Kienesberger; Hanna Sprenger; Stella Wolfgruber; Bettina Halwachs; Gerhard G Thallinger; Guillermo I Perez-Perez; Martin J Blaser; Ellen L Zechner; Gregor Gorkiewicz (PLoS ONE)
Campylobacter fetus are important animal and human pathogens and the two major subspecies differ strikingly in pathogenicity. C. fetus subsp. venerealis is highly niche-adapted, mainly infecting the genital tract of cattle. C. fetus subsp. fetus has a wider host-range, colonizing the genital- and intestinal-tract of animals and humans. We report the complete genomic sequence of C. fetus subsp. venerealis 84-112 and comparisons to the genome of C. fetus subsp. fetus 82-40. Functional analysis of genes predicted to be involved in C. fetus virulence was performed. The two subspecies are highly syntenic with 92% sequence identity but C. fetus subsp. venerealis has a larger genome and an extra-chromosomal element. Aside from apparent gene transfer agents and hypothetical proteins, the unique genes in both subspecies comprise two known functional groups: lipopolysaccharide production, and type IV secretion machineries. Analyses of lipopolysaccharide-biosynthesis genes in C. fetus isolates showed linkage to particular pathotypes, and mutational inactivation demonstrated their roles in regulating virulence and host range. The comparative analysis presented here broadens knowledge of the genomic basis of C. fetus pathogenesis and host specificity. It further highlights the importance of surface-exposed structures to C. fetus pathogenicity and demonstrates how evolutionary forces optimize the fitness and host-adaptation of these pathogens.